The NO2 camera based on gas correlation spectroscopy - Kuhn, Leon; Kuhn, Jonas; Wagner, Thomas; Platt, Ulrich (Atmospheric measurement techniques, 2022)
Spectroscopic methods have proven to be reliable and of high selectivity by utilizing the characteristic spectral absorption signature of trace gases such as NO2. However, they typically lack the spatiotemporal resolution required for real-time imaging measurements of NO2 emissions. We propose imaging measurements of NO2 in the visible spectral range using a novel instrument, an NO2 camera based on the principle of gas correlation spectroscopy (GCS). For this purpose two gas cells (cuvettes) are placed in front of two camera modules. One gas cell is empty, while the other is filled with a high concentration of the target gas. The filled gas cell operates as a non-dispersive spectral filter to the incoming light, maintaining the two-dimensional imaging capability of the sensor arrays. NO2 images are generated on the basis of the signal ratio between the two images in the spectral window between 430 and 445 nm, where the NO2 absorption cross section is strongly structured. The capabilities and limits of the instrument are investigated in a numerical forward model. The predictions of this model are verified in a proof-of-concept measurement, in which the column densities in specially prepared reference cells were measured with the NO2 camera and a conventional differential optical absorption spectroscopy (DOAS) instrument. Finally, results from measurements at a large power plant, the Grosskraftwerk Mannheim (GKM), are presented. NO2 column densities of the plume emitted from a GKM chimney are quantified at a spatiotemporal resolution of 1/12 frames per second (FPS) and 0.9m x 0.9m. A detection limit of 2 . 10(16) molec. cm(-2) was reached. An NO2 mass flux of F-m = (7.4 +/- 4.2) kg h(-1) was estimated on the basis of wind speeds obtained from consecutive images. The instrument prototype is highly portable for building costs of below EUR 2000.